Brief Report: The Value of a Patient Global Assessment of Disease Activity in Granulomatosis With Polyangiitis (Wegener's). Issue 2 (February 2014) - Tomasson, Gunnar; Davis, John C.; Hoffman, Gary S.; McCune, W. Joseph; Specks, Ulrich; Spiera, Robert; St.Clair, E. William; Stone, John H.; Merkel, Peter A.
<x xml:space="preserve">Abstract</x> Objective To 1) describe the distribution of patient global assessment (PtGA) scores of disease activity in patients with granulomatosis with polyangiitis (GPA; Wegener's), 2) explore the discordance between PtGA scores and physician global assessment (PhGA) scores of disease activity, and 3) explore whether PtGA scores during disease remission are associated with future disease relapse. Methods Data from the Wegener's Granulomatosis Etanercept Trial (WGET) were used. PtGA and PhGA scores were assessed on 100‐mm visual analog scales (VAS). Presence of active disease was determined using the Birmingham Vasculitis Activity Score for WG (BVAS/WG), and remission was defined as a BVAS/WG score of 0. Disease relapse was defined as a BVAS/WG score of >0 after remission had been achieved. Discordance between PtGA and PhGA scores was defined as a difference of ≥20 points between the two measures. Mixed linear models were used in longitudinal analysis of PtGA scores. Results Data were obtained from 180 patients in the WGET cohort, seen at a total of 1, 719 study visits. The mean ± SD PtGA and PhGA disease activity scores (on 100‐mm VAS) at baseline were 64.2 ± 27.4 and 55.5 ± 23.4, respectively. PtGA–PhGA discordance occurred in 53% of patients at baseline, and this was inversely associated with newly diagnosed disease (as opposed to relapsing disease) at baseline (odds ratio 0.37, 95% confidence interval [95% CI] 0.20–0.68) but not with age, sex, or presence of renal or pulmonary disease. Patients were in disease remission during 62% of the study visits. The mean PtGA score during visits immediately prior to relapse was 4.52 points higher (95% CI 0.66–8.4) than that at other remission visits (P = 0.03). Conclusion PtGA–PhGA discordance is common in GPA. A rise in the PtGA disease activity score during times defined by physicians as periods of remission is associated with subsequent occurrence of disease relapse. These findings support the addition of PtGA as an outcome measure for GPA.